2021
DOI: 10.1158/1078-0432.ccr-20-4691
|View full text |Cite
|
Sign up to set email alerts
|

Camrelizumab Combined with Chemotherapy Followed by Camrelizumab plus Apatinib as First-line Therapy for Advanced Gastric or Gastroesophageal Junction Adenocarcinoma

Abstract: Purpose: Capecitabine plus oxaliplatin (CAPOX) is one of the standard first-line treatments for unresectable, advanced, or metastatic gastric or gastroesophageal junction (G/GEJ) adenocarcinoma. Camrelizumab shows promising antitumor activity in advanced or metastatic G/GEJ adenocarcinoma in a phase I study. We reported the outcomes of cohort 1 in a multicenter, open-label, phase II trial, which assessed camrelizumab in combination with CAPOX followed by camrelizumab plus apatinib as a first-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 43 publications
5
69
0
Order By: Relevance
“…We retrospectively collected and analyzed the data of 84 metastatic GI patients treated with ICB in the Department of GI Oncology, Peking University Cancer Hospital & Institute (PUCH), between August 1, 2015, and May 24, 2019. The blood samples and tumor tissues were additionally collected from the clinical trials (NCT02825940 [ 19 ], NCT02915432 [ 20 ], NCT03167853 [ 21 ], NCT03472365 [ 22 ], NCT02872116 [ 23 ], NCT03713905 [ 24 ], NCT03736889 [ 25 ], NCT03667170 [ 26 ], and CTR20160872 [ 27 ]) and were newly analyzed. All patients met the following criteria: (1) diagnosis of metastatic gastrointestinal cancer with failed standard treatment; (2) patients received at least one cycle of PD-1/PD-L1 inhibitors; and (3) patients with eligible blood samples, tumor sample, and adequate clinical information.…”
Section: Methodsmentioning
confidence: 99%
“…We retrospectively collected and analyzed the data of 84 metastatic GI patients treated with ICB in the Department of GI Oncology, Peking University Cancer Hospital & Institute (PUCH), between August 1, 2015, and May 24, 2019. The blood samples and tumor tissues were additionally collected from the clinical trials (NCT02825940 [ 19 ], NCT02915432 [ 20 ], NCT03167853 [ 21 ], NCT03472365 [ 22 ], NCT02872116 [ 23 ], NCT03713905 [ 24 ], NCT03736889 [ 25 ], NCT03667170 [ 26 ], and CTR20160872 [ 27 ]) and were newly analyzed. All patients met the following criteria: (1) diagnosis of metastatic gastrointestinal cancer with failed standard treatment; (2) patients received at least one cycle of PD-1/PD-L1 inhibitors; and (3) patients with eligible blood samples, tumor sample, and adequate clinical information.…”
Section: Methodsmentioning
confidence: 99%
“…The findings suggested that apatinib combined with paclitaxel-based chemotherapy might be effective and tolerable in patients with chemotherapy-refractory GC (10); apatinib combined with S-1 was not superior to other chemotherapy regimens as first-line therapy for advanced GC (12); apatinib plus neoadjuvant chemotherapy followed by resection in patients with locally advanced gastric adenocarcinoma showed favorable activity and manageable safety (11); apatinib showed promising efficacy and an acceptable safety profile in patients with advanced alpha-fetoprotein-producing GC (13). According to the results of a recent clinical trial, apatinib combined with chemotherapy and PD-1 inhibitor exerted encouraging antitumor activity and manageable toxicity as first-line therapy for patients with advanced or metastatic gastric or gastroesophageal junction adenocarcinoma (14). In general, apatinib is currently considered a third-line or higher-line treatment option for advanced GC in China and is being continuously tested in combination therapies and various treatment scenarios for GC.…”
Section: Gcmentioning
confidence: 99%
“…The overall response rate was 58.3%. The median response duration was 5.7 months, the median OS 14.9 months, and the median PFS 6.8 months (6). This is the first report of a CCR in a patient with an advanced gastric adenocarcinoma treated with camrelizumab plus chemotherapy followed by camrelizumab plus capecitabine first-line therapy.…”
Section: Discussionmentioning
confidence: 81%
“…However, the effectiveness of chemotherapy alone is limited. In patients with advanced gastric adenocarcinomas, immunotherapy combined with chemotherapy affords stronger anti-tumor activity as first-line therapy than does chemotherapy alone ( 5 , 6 ). In our present case, the patient achieved a clinical complete response (CCR) after six cycles of treatment with carrizumab plus capecitabine, and her progression-free survival (PFS) is currently 14 months on maintenance treatment with carrizumab plus capecitabine.…”
Section: Introductionmentioning
confidence: 99%